Hubungan Tingkat Kecemasan Dengan Kepuasan Kerja Perawat Di Ruang Rawat Inap Bougenville RSUD Leuwiliang Tahun 2021: Relationship of Anxiety Level with Nurses’ Job Satisfaction in the Bougenville ICU at Leuwiliang Hospital in 2021 - Susanti, Susi (Dohara POAJ, 2022)
Introduction: Anxiety is a worry or feeling of fear experienced by a nurse. Methods: The research method used is descriptive correlation with a cross sectional approach. The population in this study were 30 nurses. Samples were taken using a total sampling technique of 30 nurses. The instruments used were the HADS (Hospital Anxiety and Depression Scale) questionnaire and the Minnesota Satisfaction Questionnaire (MSQ). Results Data analysis used univariate and bivariate data using the Chi-Square test. Results: The results of this study indicate that there is a relationship between the level of anxiety (p-value = 0.026) and job satisfaction of nurses at Bougenville Hospital Leuwiliang in 2021. Discussion: Hospitals are expected to do regular refreshments to improve the quality of nurses so that it is hoped that the level of nurses will decrease along with the increase in knowledge and skills. This can also increase the job satisfaction of nurses so that they can always work optimally.